Propuesta metodológica de intervención Urbana para la creación de Barrios Sostenibles en Riobamba - Gavilanes Vargas, Michelle Monserrath (2019)
Latin American cities have experienced rapid population and regional growth over the years, evidencing high levels of pollution, depletion of natural resources and degradation of green areas, making them increasingly less sustainable. This leads to a need to introduce a new model of urban development that consists of the creation of sustainable neighborhoods. The proposal this type of neighborhoods based on new theories about the model of compact city to which we must aim. Taking into account that a sustainable neighborhood is a neighborhood with participatory and ecological criteria where a group of people with a vision in collectively organized in order to improve their quality of life, achieve human well-being and create a local identity. The purpose of this research is that through criteria and indicators selected based on an analysis and review of bibliographic international, national and local sources has created a methodology of diagnosis and evaluation of the current situation regarding the sustainability of the neighborhoods of the Riobamba city. They chose 31 indicators grouped into five areas: urban structure, transportation, urban metabolism, and socioeconomic and cultural aspects each one with their calculation method and evaluation parameters that will be used to measure the sustainability of the neighborhood. The results of this diagnosis constitute a useful tool to define strategies and guidelines that allow planning the city more sustainable with the creation of eco-neighborhoods. Understanding that the term creation does not refer only to a planning that starts from scratch, because the challenge it does not lie in the design of new settlements and cities but in the redesign of what already exists to meet the objectives of sustainability.